Sectoral specialisation and growth rate differences among integrated economies - André Lorentz (Scuola Superiore Sant'Anna, Laboratory of Economics and Management (LEM), 2004)
This paper addresses the question of sectoral specialisation mechanisms and effects on growth rate differences providing an alternative approach to endogenous growth processes. The framework we choose draws on the Kaldorian cumulative causation approach to growth and the evolutionary modelling of technical change and industrial dynamics. The framework developed in the paper is used to consider the following issues: First, the paper addresses the question of sectoral specialisation as an emergent property of the dynamics generated by the model, focusing on the mechanisms leading to and sustaining specialisation patterns. These mechanisms are linked to technology but also demand. Second, the paper investigates the relationship between specialisation patterns and growth rate differences among economies. Specialisation can lead to increases in growth rate differences among economies. We then try to sort out the mechanisms inducing this pattern.
Keywords: O41; O30; F43; 330; Sectoral Specialisation; Economic Growth; Technical Change; Cumulative causation; Evolutionary modelling; Arbeitsteilung; Neue Wachstumstheorie; Wirtschaftswachstum; Technischer Fortschritt; Mikroökonomische Fundierung; Simulation; Theorie